Rút gọn các biểu thức sau a) sin ( 45^0 + alpha ) - cos ( 45^0 + alpha)/sin ( 45^0 + alpha + cos ( 5^0 + alpha ); b) sin 2alpha + sin alpha/1 + cos 2alpha + cos alpha; c) 1 + cos al
33
08/09/2024
Rút gọn các biểu thức sau
a) sin(45∘+α)−cos(45∘+α)sin(45∘+α)+cos(45∘+α);
b) sin2α+sinα1+cos2α+cosα;
c) 1+cosα−sinα1−cosα−sinα;
d) sinα+sin3α+sin5αcosα+cos3α+cos5α.
Trả lời
Lời giải
a) sin(45∘+α)−cos(45∘+α)sin(45∘+α)+cos(45∘+α)
=(sin45∘cosα+cos45∘sinα)−(cos45∘cosα−sin45∘sinα)(sin45∘cosα+cos45∘sinα)+(cos45∘cosα−sin45∘sinα)
=(√22cosα+√22sinα)−(√22cosα−√22sinα)(√22cosα+√22sinα)+(√22cosα−√22sinα)
=√2sinα√2cosα=tanα.
b) sin2α+sinα1+cos2α+cosα
=2sinαcosα+sinα1+(2cos2α−1)+cosα
=2sinα(cosα+1)2cosα(cosα+1)
=sinαcosα=tanα.
c) 1+cosα−sinα1−cosα−sinα
=1+(2cos2α2−1)−2sinα2cosα21−(1−2sin2α2)−2sinα2cosα2
=2cos2α2−2sinα2cosα22sin2α2−2sinα2cosα2
=2cosα2(cosα2−sinα2)2sinα2(sinα2−cosα2)
=cosα2(cosα2−sinα2)sinα2[−(cosα2−sinα2)]
=−cosα2sinα2=−cotα2.
d) sinα+sin3α+sin5αcosα+cos3α+cos5α
=(sin5α+sinα)+sin3α(cos5α+cosα)+cos3α
=2sin5α+α2cos5α−α2+sin3α2cos5α+α2cos5α−α2+cos3α
=2sin3αcos2α+sin3α2cos3αcos2α+cos3α
=sin3α(2cos2α+1)cos3α(2cos2α+1)
=sin3αcos3α=tan3α.